Determinants and dynamics of food insecurity during COVID-19 in rural Bangladesh. (May 2021) - Ahmed, Firoz; Islam, Asad; Pakrashi, Debayan; Rahman, Tabassum; Siddique, Abu
Highlights: We examine food insecurity situation during COVID-19 in rural Bangladesh. 90% of households experienced loss of income due to lockdown. COVID-19 led to a drastic increase in income loss and food insecurity. Farm and day laborers were initially affected the most. Food insecurity increased significantly over time. Abstract: COVID-19 has threatened food security of the poor due to the lockdown of markets amidst poor institutions and lack of social safety nets in the developing world. To provide rapid evidence on the determinants and dynamics of food insecurity and to understand the coping strategies adopted by rural households during the pandemic, we carried out a telephone survey of roughly 10, 000 rural households in Bangladesh, three weeks after the country went into lockdown. We found that roughly 90% of households reported experiencing a negative income shock after the countrywide lockdown was implemented. Households that primarily depend on daily casual labor for their income were affected the most, while households with regular jobs were affected the least in terms of food insecurity. Households adversely hit by income shock due to the pandemic were also found to rely more on past savings, food stocks, and loans from various sources to cope with the food crisis. When we followed-up 2402 households, about 3 to 4 weeks after the first survey, to understand the dynamics of food insecurity, we found that food insecurity increased significantly across households and began affecting groups that were in an advantageous position during the first survey. This poses a threat to the poor as food security has already worsened since the crisis hit and would presumably worsen further in the future unless rapid measures are taken to attenuate it at the earliest.